الشراكة المحلية كآلية لتحقيق التنمية المحلية الراشدة على ضوء قانون البلدية 11_10 - - صغيري يونس - يسعد رابح (جامعة المسيلة, 2024)
The concept of local partnership in achieving local development emphasizes cooperation between different local entities to plan and implement development programs. This partnership aims to provide better services to citizens through sharing responsibilities and utilizing resources. It is rooted in the idea that active local entities are in a better position to understand and address challenges in their communities. Within the context of local law, these partnerships are often given an institutional character to ensure that local governance is participatory, comprehensive, and responsive to the community's needs. The law may define the framework of these partnerships to clarify and detail the roles and responsibilities of each party, providing guiding principles for cooperation and coordination. The ultimate goal of local partnerships under local law is to enhance sustainable local development that benefits everyone, ensuring that development initiatives are based on local realities and receive support and participation from all local actors and stakeholders. This approach is also seen as a means to strengthen governance. Therefore, the Algerian government has embraced the concept of local partnership as a mechanism for achieving local development and establishing the foundations of good governance. This has led the Algerian legislator to issue Law No. 11/10 concerning municipalities. Furthermore, this study aims to highlight the role of local partners (private sector, civil society, local media) as a mechanism for achieving local development in light of Municipal Law 11/10
Keywords: local partnership; local development; private sector; civil society; local media